2016
DOI: 10.1159/000445066
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Experience of Modified Transperineal Template Guided Saturation Biopsy Under General Anaesthesia and without Prophylactic Catheterisation

Abstract: Results of patient feedback questionnaire following transperineal template guided saturation biopsy (TPSB) without prophylactic catheterisation. Introduction and Objective: TPSB is increasingly utilised in the diagnosis and characterisation of prostate cancer. However, there is little data on patient experience after undergoing this procedure. We circulated a questionnaire to 511 consecutive patients from July 2007 to December 2014 and now analyse the responses. Materials and Methods: The mean age for the coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Moreover, they are well tolerated and have only minor, temporarily side effects like hematuria, short-term catheterization, erectile deterioration, or fever with no septic complications being reported [32] . Thus, patients seem to handle them at least as good as conventional TRUS biopsy [33] . Our data support the hypothesis that next to MRI-invisible tumors one main reason for negative TB are targeting errors [34] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they are well tolerated and have only minor, temporarily side effects like hematuria, short-term catheterization, erectile deterioration, or fever with no septic complications being reported [32] . Thus, patients seem to handle them at least as good as conventional TRUS biopsy [33] . Our data support the hypothesis that next to MRI-invisible tumors one main reason for negative TB are targeting errors [34] .…”
Section: Discussionmentioning
confidence: 99%
“…Patient reported experience also demonstrates that the procedure is well tolerated and caries acceptable postoperative symptom rates [17]. Briefly, all procedures were performed under GA, with a side viewing, biplanar implant probe (BK Medical, Herlev, Denmark) attached to a brachytherapy stepping unit (DK Technologies®, Barum,Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Observation after 28 days following TTPB indicated that 310 (0.31%) developed sepsis 757 (0.77%) developed an infection and 950 (0.96%) developed UTI [ 9 ]. Haematuria is a common manifestation of blood loss after TTPB [ 10 , 11 ]. Urinary retention is by far the most common complication observed after TTPB with reported occurrence rates of 16% ( n = 35) [ 10 ], 6.3% ( n = 110) [ 12 ], and 7.9% ( n = 379) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%